2021
DOI: 10.3389/fimmu.2021.688879
|View full text |Cite
|
Sign up to set email alerts
|

Functional Contribution and Targeted Migration of Group-2 Innate Lymphoid Cells in Inflammatory Lung Diseases: Being at the Right Place at the Right Time

Abstract: During the last decade, group-2 innate lymphoid cells (ILC2s) have been discovered and successfully established as crucial mediators of lung allergy, airway inflammation and fibrosis, thus affecting the pathogenesis and clinical course of many respiratory diseases, like for instance asthma, cystic fibrosis and chronic rhinosinusitis. As an important regulatory component in this context, the local pulmonary milieu at inflammatory tissue sites does not only determine the activation status of lung-infiltrating IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 168 publications
(249 reference statements)
0
6
0
Order By: Relevance
“…Lung ILC2 cells are located close to the epithelial lining of large and small airways, and these cells were significantly enriched in the BAL fluid of vimentin-immunized mice. Although the absolute numbers of ILC2 are small, they are the early responders to lung inflammation and affect the clearing of pathogens and tissue repair [ 40 ]. Analysis of BAL from sarcoidosis patients for the presence of ILC2 will substantiate their role in disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Lung ILC2 cells are located close to the epithelial lining of large and small airways, and these cells were significantly enriched in the BAL fluid of vimentin-immunized mice. Although the absolute numbers of ILC2 are small, they are the early responders to lung inflammation and affect the clearing of pathogens and tissue repair [ 40 ]. Analysis of BAL from sarcoidosis patients for the presence of ILC2 will substantiate their role in disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…These imaging methods were also used to explore the state and function of innate lymphoid cells (ILC) in the gut and to determine that ILC2 are migratory, in contrast to the general view in the field 39,40 . This new insight into ILC2 biology has been confirmed and extended by others 41 …”
Section: Advances In the Last Decade Using Ivmmentioning
confidence: 94%
“…39,40 This new insight into ILC2 biology has been confirmed and extended by others. 41 Very recently, we have used multiplex imaging, together with IVM, to extend this concept of immune cell spatial polarization to the liver. Gola et al 42 found that the distribution of several immune populations, including Kupffer cells, CD8+ memory T cells, and NK T cells, all showed a higher density near the portal triad as compared to the central vein within a hepatic lobule.…”
Section: Advan Ce S In the L A S T Dec Ade Us Ing Ivmmentioning
confidence: 99%
“…Innate lymphoid cells (ILCs) are a heterogeneous population of lymphocytes that lack common lineage markers. ILCs are differentiated by their transcription factor expression profiles and cytokine production capabilities ( Wirtz et al, 2021 ). ILCs are categorized into three major subpopulations, ILC1s, ILC2s, and ILC3s, which are the innate counterparts to CD4 + Th1, Th2, and Th17 cells ( Artis and Spits, 2015 ).…”
Section: Introductionmentioning
confidence: 99%